Platelet transfusion in neonatal intensive care units of 22 European countries: a prospective observational study - Houben, Nina A M; Lopriore, Enrico; Fijnvandraat, Karin; Caram-Deelder, Camila; Carrascosa, Marta Aguar; Beuchée, Alain; Brække, Kristin; Cardona, Francesco; Debeer, Anne; Domingues, Sara; Ghirardello, Stefano; Grizelj, Ruza; et al. (The Lancet regional health. Europe, 2024)
BACKGROUND: Platelet transfusions are given to preterm infants with severe thrombocytopenia aiming to prevent haemorrhage. The PlaNeT2/MATISSE trial revealed higher rates of mortality and/or major bleeding in preterm infants receiving prophylactic platelet transfusions at a platelet count threshold of 50 × 109/L compared to 25 × 109/L. The extent to which this evidence has been incorporated into clinical practice is unknown, thus we aimed to describe current neonatal platelet transfusion practices in Europe. METHODS: We performed a prospective observational study in 64 neonatal intensive care units across 22 European countries between September 2022 and August 2023. Outcome measures included observed transfusion prevalence rates (per country and overall, pooled using a random effects Poisson model), expected rates based on patient-mix (per country, estimated using logistic regression), cumulative incidence of receiving a transfusion by day 28 (with death and discharge considered as competing events), transfusion indications, volumes and infusion rates, platelet count triggers and increment, and adverse effects. FINDINGS: We included 1143 preterm infants, of whom 71 (6.2%, [71/1143]) collectively received 217 transfusions. Overall observed prevalence rate was 0.3 platelet transfusion days per 100 admission days. By day 28, 8.3% (95% CI: 5.5-11.1) of infants received a transfusion. Most transfusions were indicated for threshold (74.2%, [161/217]). Pre-transfusion platelet counts were above 25 × 109/L in 33.1% [53/160] of these transfusions. There was significant variability in volume and duration. INTERPRETATION: The restrictive threshold of 25 × 109/L is being integrated into clinical practice. Research is needed to explore existing variation and generate evidence for various aspects including optimal volumes and infusion rates. FUNDING: Sanquin, EBA, and ESPR.
Keywords: Neonatal intensive care unit; Epidemiology; Neonatology; Platelet transfusion; Europe; Preterm infants; Thrombocytopenia